Impact of diabetes mellitus on patients affected by oral lichen planus: a retrospective study - Tenore, Gianluca; Mohsen, Ahmed; Ricciotti, Andrea; Piombarolo, Giordano; Podda, Gian Marco; Di Gioia, Cira Rosaria Tiziana; Romeo, Umberto (Frontiers in Oral Health, 2025)
IntroductionThe association between diabetes mellitus (DM) and oral lichen planus (OLP) has been widely reported. However, most of the studies focused on epidemiological aspects and shared inflammatory pathways, with few exploring the consequences of this association on the clinical course of OLP. The study aims to retrospectively observe the impact of DM on the clinical presentation and management strategy of OLP.MethodsA total of 97 OLP patients were retrieved from the Department database. The patients were distributed into two groups: OLP patients with DM “test group” (n = 47) and OLP patients without DM “control group” (n = 50). The descriptive and statistical analyses were performed on the variables related to the clinical presentation of OLP, the management of OLP, and the general and demographic information.ResultsRegarding primary outcomes related to the clinical presentation variables, DM patients were symptomatic and more susceptible to present atrophic lesions at the first visit, compared to those without DM with a statistical significance (p = 0.0017 and p = 0.0016 respectively). Buccal mucosa was generally the most affected site in both groups and was notably higher in patients with DM (p = 0.0286). Regarding the management variables, DM patients were subjected to a higher number of follow-ups per year (p = 0.0420), a higher number of prescribed general treatments per year (p = 0.0006), and a higher number of prescribed non-cortisone-based treatments per year (p = 0.0001). In regard to the secondary outcomes related to the general and demographic variables, a statistically significant difference was observed with concomitant diseases, where patients with DM were more susceptible to concomitant diseases (p = 0.0321), particularly cardiopathy (p = 0.0422), arterial hypertension (p = 0.0418), dyslipidemia (p = 0.0411), and coagulopathy (p = 0.0411).DiscussionDM patients were highly presented with symptomatic OLP and showed a difference in the management strategy where more follow-ups and treatment prescriptions were needed. It seems that the clinician should consider DM as an essential co-factor that may influence the management procedures of OLP. Considering interdisciplinary management and involving endocrinologists may add significant value to the OLP management process.